2018
DOI: 10.1007/s10552-018-1017-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-strengthening and aerobic activities and mortality among 3+ year cancer survivors in the U.S.

Abstract: While muscle-strengthening activities by themselves do not appear to reduce mortality risks, such activities may provide added cancer-specific survival benefits to 3+ year cancer survivors who are already aerobically active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…Approximately 80% of German adults did not meet the nationally recommended physical activity guidelines of ≥ 150 minutes per week of aerobic MVPA and MSE ≥ 2 days per week. Considering that evidence that combined aerobic MVPA-MSE is independently associated with a multiple beneficial health outcomes [13,14,22,26,30], our findings suggest the need for immediate public health action to address physical inactivity in Germany.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Approximately 80% of German adults did not meet the nationally recommended physical activity guidelines of ≥ 150 minutes per week of aerobic MVPA and MSE ≥ 2 days per week. Considering that evidence that combined aerobic MVPA-MSE is independently associated with a multiple beneficial health outcomes [13,14,22,26,30], our findings suggest the need for immediate public health action to address physical inactivity in Germany.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, recent epidemiological studies have shown that compared to meeting one guideline alone, meeting both aerobic MVPA-MSE guidelines is prospectively associated with lower risk of allcause mortality [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Yet the majority of cancer survivors are not meeting these recommended PA guidelines [1113]. Previous research exploring why cancer survivors are not physically active has identified a variety of barriers to PA, such as cancer treatment-related side effects, pain, fatigue, comorbid medical conditions, time, and motivation [1419].…”
Section: Introductionmentioning
confidence: 99%
“…They should aim to participate in moderate to vigorous exercise for at least 150 min/wk, and strength training should be a part of their regimen . A recently published analysis of National Health Interview Survey linked mortality data suggested that cancer survivors who reported adhering to the complete ACS PA guidelines had a significantly lower risk of all‐cause, cancer‐specific, and cardiovascular disease–specific mortality …”
Section: Introductionmentioning
confidence: 99%